The psychological state and mental health of elite adolescent athletes: the mediation effect of resilience - Chang, K. T.; Wang, C. H.; Yang, C. T. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
The mental health of adolescent athletes is important for their performance and career growth as they experience both physical and psychological development. Research has shown that stable psychological state helps athletes maintain mental health during stressful situations. The Peace of Mind (PoM) Index is a measure of psychological well-being in Asian cultures. It encompasses a state of low arousal, happiness, harmony, and an overall feeling of peacefulness within oneself. High PoM individuals are characterized by a stable emotional state, which allows them to quickly readjust their psychological condition without experiencing significant fluctuations. Hence, psychological resilience, the ability to maintain psychological stability and return to normal during adverse situations, is believed to play a significant role in the relationship between psychological state and mental health. To clarify the role of the resilience, we hypothesize that PoM will affect the mental health of adolescent elite athletes via resilience. In this study, 31 male adolescent soccer players (mean age: 16.61 ± 0.84 years) were recruited. The psychological state, resilence, and mental health were measured with POM, Resilience Scale for Adults (RSA), and Becks Depression Inventory scale (BDI-II), respectively. Using the bootstrapping method (with 5000 times) of Process 4.2 SPSS macro by Hayes (2022), the findings of the simple mediation analysis indicated that the indirect effect of PoM on BDI-II through RSA was statistically significant and in a negative direction. The bootstrapping result also confirmed the Sobel test, showing that the indirect effect was significant with the 95% confidence interval not including zero [-5.11 - -0.07]. The results emphasize the vital role of resilience in maintaining a stable psychological state and low levels of depression among elite adolescent athletes. Specifically, elite adolescent athletes with high resilience are found to possess a more stable psychological state and exhibit lower levels of depression. Future research can explore intervention for enhancing psychological resilience, thus improving the mental well-being of adolescent athletes.